'All that's left': John Koethe's Traces of Experience. (April 2014) - Johnson, Andrew
<x content-type="archive" xml:space="preserve">Abstract</x> Following in the tradition of Wallace Stevens and John Ashbery, John Koethe's poems are philosophical, meditative explorations in a sceptical and ironic mode. He is among the first rank of contemporary American poets as well as being a published philosopher who teaches at the University of Wisconsin. This article focuses on the issues of memory and experience raised in his work (a poetics of the trace), focusing in particular on poems from his two most recent books, Ninety-Fifth Street (2009) and Sally's Hair (2006). A poetics of the trace, as I argue, puts into question the possibility of poetry as a 'pure' or 'simple' representation of a lost presence. Although this could be registered as a loss of empirical certainty, such poetics also may be linked with a more profound 'responsibility, ' or moral sense, in the personal lyric.